A prospective study of phage types & biotypes of Salmonella enterica serotype Typhi isolated from hospitalized children in Kolkata, India - Saha, M R; Palit, A; Chatterjee, N S; Dutta, P; Mitra, U; Bhattacharya, S K (Indian journal of medical research (New Delhi, India : 1994), 2003)
Kolkata and its suburbs in eastern India faced an epidemic of typhoid fever in 1990. A prospective, hospital and laboratory based study over a period of 12 yr (1990-2001), on the phage typing and biotyping pattern of Salmonella enterica serotype Typhi was carried out, to see if there has been a change. A total of 338 S. enterica serotype Typhi isolates from 1491 blood samples were phage typed and biotyped. The mean age of isolation was calculated. The age distribution of subjects (neonates to 12 yr) has been analysed. Of the 338 (22.7%) isolates obtained, eight different S. enterica serotype Typhi phage types were detected. Biotype I (95.8%) was more prevalent as compared to biotype II (4.1%). Phage type E1 was the commonest phage type in Kolkata and its suburbs. The mean age at isolation was found to be 6.7 +/- 3.3 yr. Biotype I was predominant and it was of interest that all strains of phage type E1 belonged to biotype I.